The evolution of a Pluto-like system during the migration of the ice giants - Pires, Pryscilla [UNESP]; Giuliatti Winter, Silvia M. [UNESP]; Gomes, Rodney S. (Elsevier B.V., 2015)
The planetary migration of the Solar System giant planets in the framework of the Nice model (Tsiganis, K., Games, R., Morbidelli, A., Levison, H.F. [2005]. Nature 435,459-461; Morbidelli, A., Levison, H.F., Tsiganis, K., Gomes, R. [2005]. Nature 435, 462-465; Gomes, R., Levison, H.F., Tsiganis, K., Morbidelli, A. [2005]. Nature 435, 466-469) creates a dynamical mechanism which can be used to explain the distribution of objects currently observed in the Kuiper belt (e.g., Levison, H.F., Morbidelli, A., Vanlaerhoven, C., Gomes, R., Tsiganis, K. [2008]. Icarus 196, 258-273). Through this mechanism the planetesimals within the disk, heliocentric distance ranging from beyond Neptune's orbit to approximately 34 AU, are delivered to the belt after a temporary eccentric phase of Uranus and Neptune's orbits. We reproduced the mechanism proposed by Levison et al. to implant bodies into the Kuiper belt. The capture of Pluto into the external 3:2 mean motion resonance with Neptune is associated with this gravitational scattering model. We verified the existence of several close encounters between the ice giants and the planetesimals during their outward radial migration, then we believe that the analysis of the dynamical history of the plutonian satellites during this kind of migration is important, and would provide some constrains about their place of formation - within the primordial planetesimal disk or in situ. We performed N-body simulations and recorded the trajectories of the planetesimals during close approaches with Uranus and Neptune. Close encounters with Neptune are the most common, reaching approximately 1200 in total. A Pluto similarly sized body assumed the hyperbolic trajectories of the former primordial planetesimal with respect to those giant planets. We assumed the current mutual orbital configuration and sizes for Pluto's satellites, then we found that the rate of destruction of systems similar to that of Pluto with closest approaches to Uranus or Neptune <0.10 AU is 40%, i.e. these close approaches can lead to ejections of satellites or to changes in the satellites eccentricities at least 1 order of magnitude larger than the currently observed. However, we also found that the number of closest approaches which the minimum separation to Uranus or Neptune <0.10 AU is negligible, reaching 6%. In the other 60% of close encounter histories with closest approaches >0.10 AU, none of the systems have been destroyed. The latter sample concentrates 94% of closest approaches with the ice giants. Recall that throughout the early history of the Solar System giant impacts were common (McKinnon, W.B. [1989]. Astrophys. J. 344, L41-L44; Stern, A. [1991]. Icarus 90; Canup, R.M. [2005]. Science 307, 546-550). Also, impacts capable of forming a binary like Pluto-Charon can occur possibly prior to 0.5-1 Gyr (Kenyon, SJ., Bromley, B.C. [2014]. Astron. J. 147, 8), and small satellites such as Nix and Hydra can grow in debris from the giant impact (e.g., Canup, R.M. [2011]. Astron. J. 141, 35). Thus, we conclude that if Pluto and its satellites were emplaced into the KB from lower heliocentric orbits, then the Pluto system could survive the encounters that may have happened for emplacement of the Plutinos through the mechanism proposed by Levison et al. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Planetary dynamics; Trans-Neptunian objects; Pluto, satellites